Treatment of autoimmune hepatitis: what is the optimal end point on follow-up biopsy?. (13th March 2011) - Dhaliwal, H K; Hoeroldt, B S; Dube, A; McFarlane, E; Karajeh, M A; Gleeson, D C
Abstract : Introduction: The authors have reported1 that following immunosuppressive treatment of Autoimmune Hepatitis (AIH), many patients fail to achieve histological remission (necro-inflammatory score (NIS) ≥3), despite attaining biochemical remission (normal serum ALT). A recent report2 suggests that, following treatment, a NIS≥5 is not associated with fibrosis progression and hence, may be an acceptable treatment outcome.2 The authors therefore aimed to assess the associations of NIS on follow-up biopsy within the range 0–5, with change in fibrosis and survival. Methods: The authors studied 114 patients with AIH by IAIHG criteria (81 definite, 94 female, mean age 48.7±1.7 years), treated initially with reducing dose prednisolone and 1 mg/kg azathioprine, who had achieved normal serum ALT and a NIS between 0 and 5 on follow-up biopsy (performed at median (range) 2.16 (0.65–13.67) years) after diagnosis (paired diagnostic and follow-up biopsies available in 93 patients). Biopsies were graded using the Ishak system. Results: Fibrosis score between baseline and follow-up biopsy decreased in patients with follow-up NIS 0–3 (mean 3.4±0.24 to 2.7±0.21, n=59 p=0.001) but was unchanged in those with follow-up NIS of 4 or 5 (3.5±0.3 to 3.4±0.3, n=34 p=0.846). Fibrosis score on follow-up biopsy was higher in patients with NIS 4–5 (n=40) than with NIS 0–3 (n=72) (mean 3.3±0.3 vs 2.4±0.2, p=0.014). Regression of fibrosis was independently associated with lower NIS (p=0.014) and less portal inflammation (p=0.006) on follow-up biopsy, and with longer interval between the two biopsies (p=0.001). All cause death/transplantation rate was higher in those with NIS of 4–5 than in those with NIS 0–3 (18% vs 6% and 64% vs 24% after 10 and 20 years respectively; p<0.001) and this categorisation was independently associated with survival (p=0.001). A similar trend for liver death/transplantation just failed to reach significance (p=0.07). Conclusion: In patients with AIH treated with immunosupression, even mild histological activity (NIS 4 or 5) on follow-up biopsy is associated with more fibrosis and with reduced survival and hence may not be an optimal end point of treatment.